Beetle bliss / Nazeem Shahiry Mohd Ayub - Mohd Ayub, Nazeem Shahiry (Universiti Teknologi MARA, Kedah, 2024)
This project aims to design an armchair named Beetle Bliss, inspired by the delicate and captivating aesthetics of a ladybird. The focus is on creating a piece that provides comfort and functionality for apartment living while adding a touch of nature-inspired elegance to the interior space. Beetle Bliss will incorporate the distinct color palette, patterns, and forms associated with ladybirds, seamlessly blending organic shapes with modern design elements. This fusion will result in a unique and stylish armchair that enhances the visual appeal and ambiance of any apartment setting. The design concept revolves around capturing the essence of the ladybird's charm. Key features, such as the iconic red and black color scheme, polka dot patterns, and smooth, rounded forms, will be translated into the armchair's structure and upholstery. The name Beetle Bliss reflects the aim to evoke the beauty of ladybirds in nature, bringing a nature-inspired touch to modern interiors.